2003
DOI: 10.1097/01.tp.0000048226.28357.0d
|View full text |Cite
|
Sign up to set email alerts
|

Islet transplantation in the discordant tilapia-to-mouse model: a novel application of alginate microencapsulation in the study of xenograft rejection

Abstract: Our results indicate that rejection in the tilapia-to-mouse model follows a pattern similar to other models of discordant islet cell xenotransplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Previous studies in murine models collectively suggested that islet xenograft rejection is initiated, mediated, and dominated primarily by major histocompatibility complex (MHC) class II restricted CD4 + T cells; those T cells are activated through indirect recognition of processed SLA class I xenoantigens presented by host antigen‐presenting cells [41–43]. Those activated, xenoreactive CD4 + T cells are critical effectors in the xenorejection process [44,45] and provide the necessary signals for growth and maturation of additional effector mechanisms involving, first and foremost, macrophages [40,46]. The dominant involvement of macrophages in the effector phase of islet xenograft rejection accounts for its unique properties, strength, and complexity and calls for tailored interventions [22,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in murine models collectively suggested that islet xenograft rejection is initiated, mediated, and dominated primarily by major histocompatibility complex (MHC) class II restricted CD4 + T cells; those T cells are activated through indirect recognition of processed SLA class I xenoantigens presented by host antigen‐presenting cells [41–43]. Those activated, xenoreactive CD4 + T cells are critical effectors in the xenorejection process [44,45] and provide the necessary signals for growth and maturation of additional effector mechanisms involving, first and foremost, macrophages [40,46]. The dominant involvement of macrophages in the effector phase of islet xenograft rejection accounts for its unique properties, strength, and complexity and calls for tailored interventions [22,40,46].…”
Section: Discussionmentioning
confidence: 99%
“…A second layer that consists of alginate is applied for coverage of the unbound poly-L-lysine group [5]. Allotransplantation of microencapsulated islets in experimental animals has been extensively studied [6][7][8] while not so many studies have been published on discordant xenotransplantation [3,9]. The implantation of encapsulated islets reversed diabetes in xenotransplantation models, but the continuing function of the implants usually required immunosuppression and often generated Wbrotic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 Rejection of tilapia BBs in euthymic murine recipients is CD4 T-cell dependent and mechanistically similar to that of porcine islet xenografts. 8 However, unlike porcine and most other mammalian islets, tilapia are too phylogenetically primitive for their islets to express the dominant xenoantigen, a(1,3)Gal. 9 Because of the low metabolic needs of tilapia (n.b., tilapia are evolved to thrive in warm stagnant water nearly devoid of dissolved oxygen), tilapia BBs are an order of magnitude more hypoxia resistant than mammalian islets 10 making them ideal for survival and long-term function within encapsulation devices 11 which can be further prolonged when combined with co-stimulatory blockade.…”
Section: Introductionmentioning
confidence: 99%